A Wide and Specific Spectrum of Genetic Variants and Genotype–Phenotype Correlations Revealed by Next‐Generation Sequencing in Patients with Left Ventricular Noncompaction. Issue 9 (30th August 2017) - Wang, Ce; Hata, Yukiko; Hirono, Keiichi; Takasaki, Asami; Ozawa, Sayaka Watanabe; Nakaoka, Hideyuki; Saito, Kazuyoshi; Miyao, Nariaki; Okabe, Mako; Ibuki, Keijiro; Nishida, Naoki; Origasa, Hideki; et al.
Abstract : Background: Left ventricular noncompaction (LVNC) has since been classified as a primary genetic cardiomyopathy, but the genetic basis is not fully evaluated. The aim of the present study was to identify the genetic spectrum using next‐generation sequencing and to evaluate genotype–phenotype correlations in LVNC patients. Methods and Results: Using next‐generation sequencing, we targeted and sequenced 73 genes related to cardiomyopathy in 102 unrelated LVNC patients. We identified 43 pathogenic variants in 16 genes in 39 patients (38%); 28 were novel variants. Sarcomere gene variants accounted for 63%, and variants in genes associated with channelopathies accounted for 12%. MYH7 and TAZ pathogenic variants were the most common, and rare variant collapsing analysis showed variants in these genes contributed to the risk of LVNC, although patients carrying MYH7 and TAZ pathogenic variants displayed different phenotypes. Patients with pathogenic variants had early age of onset and more severely decreased left ventricular ejection fractions. Survival analysis showed poorer prognosis in patients with pathogenic variants, especially those with multiple variants: All died before their first birthdays. Adverse events were noted in 17 patients, including 13 deaths, 3 heart transplants, and 1 implantable cardioverter‐defibrillator insertion. Congestive heart failure at diagnosis and pathogenic variants were independent risk factors for these adverse events. Conclusions: Next‐generation sequencing revealed a wide spectrum of genetic variations and a high incidence of pathogenic variants in LVNC patients. These pathogenic variants were independent risk factors for adverse events. Patients harboring pathogenic variants showed poor prognosis and should be followed closely.